Aspectos clínicos e epidemiológicos e avaliação da disbiose cutânea em cães com dermatite atópica - Larissa Silveira Botoni (2018)
Atopic dermatitis (AD) is a chronic inflammatory, pruritic skin disease associated with allergenspecific IgE antibodies primarily against environmental allergens. AD affects several species, including dogs and humans. Pruritus is the main clinical sign of AD. In addition, atopic dogs tendto present recurrent superficial pyoderma, associated with alterations in the skin microbiome. In some cases, patients show typical clinical signs of AD, but allergen-specific IgE antibodies cannot be detected. This subtype of AD is called atopic-like dermatitis (ALD). Both the alterations in the skin microbiome of atopic dogs and the features of ALD are still poorly understood in dogs. Thus, we aimed to evaluate these two distinct parameters of AD. So, the present study was divided in two parts. In the first part, a retrospective study of the medical records of 269 dogs seen at the veterinary teaching hospital of the University of Minnesota between 2007 and 2015 was performed. Patients were divided in two groups (AD and ALD) according to the allergy testsresults. Epidemiological data, disease severity according pruritus level, number of affected body sites, maintenance treatment protocol and response to therapy were evaluated and compared between the groups. The mean pruritus level and the mean number of body sites affected across visits, the Canine Atopic Dermatitis Severity Index (CADSI) was created to assess the severity of the disease in each patient and to compare ALD and AD. In the AD group, 228 dogs (84.76%) were included and in the ALD group, 41 (15.24%). There were no significant differences between the groups in the epidemiological variables. In relation to breed predisposition, Bichon Frisé was more predisposed to developing ALD. There was no significant difference in the mean pruritus level and number of affected areas at the first visit or during treatment between groups, as well as in the outcome of these variables throughout the visits. When CADSI was compared betweengroups, there was no significant difference. In the second part, were selected prospectively seven seasonal atopic dogs, Atopic Group (GA), and ten healthy dogs, Control Group (CG). Samples were collected from the interdigital, axillary, abdominal and lumbar regions from each dog usinga sterile swab. In GC, six collections in a of four week interval were performed. In GA, the samples were collected four weeks prior the typical flare month (Pre-crisis), in the flare before starting the treatment (Flare), during the flare with treatment (Treatment) and after the flare seasonwithout treatment (Post-flare). After collection, samples were stored refrigerated for up to seven days until DNA extraction and sequencing of the 16S rRNA gene. After processing, bioinformatic and statistical analysis were performed for taxonomic evaluation and alpha and beta-diversityassessment. The most abundant phyla in all samples were Actinobacteria, Firmicutes, Fusobacteria and Proteobacteria. It was observed that the diversity of the cutaneous microbiome of atopic dogs undergoes a reduction the Pre-flare and the immunomodulatory treatment is able to reestablish it. These results are very relevant and promising as they demonstrate changes in microbiome diversity even before the inflammatory response of the disease and the restorative role of immunomodulatory therapy without the use of antimicrobials.